2013
DOI: 10.5210/ojphi.v5i1.4407
|View full text |Cite
|
Sign up to set email alerts
|

Using Syndromic Emergency Department Data to Augment Oral Health Surveillance

Abstract: ObjectiveTo utilize an established syndromic reporting system for surveillance of potentially preventable emergency department (ED) oral health visits (OHV) in New York City (NYC). IntroductionNYC Department of Health and Mental Hygiene recently reoriented its oral health care strategy to focus on health promotion and expanded surveillance. One surveillance challenge is the lack of timely OHV data; few dental providers are in our electronic health record project, and statewide utilization data are subject to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Similar to our results, Jasek and coinvestigators reported that ED dental visits in New York during 2009–2011 were highest among 18–29 year-olds. 29 Our research is the first to document that toothache is among the top reasons for younger adults to seek care in EDs. Specifically, toothache was the fifth most common chief complaint in EDs among 20–29 year-olds and the third most common for uninsured younger adults.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar to our results, Jasek and coinvestigators reported that ED dental visits in New York during 2009–2011 were highest among 18–29 year-olds. 29 Our research is the first to document that toothache is among the top reasons for younger adults to seek care in EDs. Specifically, toothache was the fifth most common chief complaint in EDs among 20–29 year-olds and the third most common for uninsured younger adults.…”
Section: Discussionmentioning
confidence: 87%
“…To that end, ED toothache visits represents a potential quality indicator for system-level barriers to dental care access or utilization within a region or population. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our study found that those aged 19 -58 were the most frequent users of the ED, it was not the only population that needed preventative dental care at the community-level and dental health care education. Toothaches, dental caries and other oral health concerns impact all ages and greatly influence one's health status, illustrating the need for improved integration of dental and medical care [15] [21] [26]. The current situation nationally and locally solidifies the need to view oral health as an importance.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the community water supply provided by the Meadville Water Authority is not fluoridated. According the Centers for Disease Control and Prevention, community water fluoridation is the most affordable and effective prevention strategy under approved fluoride levels [26]. It is important to make the change to fluoridated water and promote proper oral health from a primary prevention stance.…”
Section: National and Local Trendsmentioning
confidence: 99%